ANTIOXIDANT ACTIVITY OF METHANOL EXTRACTS FROM THE STEM BARK OF MANGROVE PLANT Rhizophora mucronata - Mahmiah Mahmiah; Giman Giman; Nanik Siti Aminah; Mulyadi Tanjung (UPT Penerbitan Universitas Jember)
Numbers of diseases such as stroke, diabetes, gout,and even cancer are caused by the reaction of freeradicals (oxidants) found in the body. Those diseasescurrently have not yet controlled. Deleteriouslifestyle, lack of exercise, or genetics can be thetrigger to this oxidant. Based on Chemotaxonomic,drugs that have been used to inhibit the oxidationprocess or termination stage of free radicals containthe active ingredient in the form of secondarymetabolites of alkaloids, phenolics, terpenoids andsteroids. For example, phenolic compounds such asflavonoids, xanthones, antioxidants and polyphenolsis a good agent because it has a structure with a highdegree of oxidation (Suares, et al, 2010).Researches related to the exploration of antioxidantactive ingredient has been more focused onsecondary metabolites found in terrestrial plants.The development of natural compounds potential ofmarine plant material such as mangrove are still notreceived much attention. Spalding et al. in 2001explained that mangroves plant in Indonesia is thehighest in the world, both in terms of quantity area(± 42 550 km2) as well as the number of species (±45 species). This basic natural resource of Indonesiamangrove is certainly valuable promisingopportunities to be expanded as a biological drug.Mangroves plant that commonly used as medicinediscovered from various species i.e: Acanthusilicifolius, Avicennia alba, Avicennia marina,Avicennia offinalis, Bruguiera cylindrical, Bruguieraexaristata, Bruguiera gymnorrhiza, Ceriops tagal,Hisbiscus tiliaceus, Ipomoea pes-capre, Lumnitzeraracemosa, Nypa fructicans, Pluchea indicaRhizophora apiculata, Rhizophora mucronata andSonneratia alba. Those plants are usually utilized asantiasma, antidiuretic, antidiabetic, reliever itching,and others. (Purnobasuki, 2004).The potential of mangroves as a drug is veryimportant to be developed considering the need fordrugs is increasing deals with the growing ofpopulation and many kinds of diseases such ascancer, hypertension, tumor diseases and diseasescaused by chemical or biological waste pollutionfrom viruses and bacteria. People are more likely tochoose drugs that are natural because relatively takefew side effects or even none at all.Several studies of mangrove plants from genusRhizophora that have antioxidant bioactivity areshown in the crude butanol extract of mangrove R.apiculata with IC50 33.34 pg / mL (Gao, 2012). Themethanol extract of R. mangle’s stem were alsodocumented to have antioxidant activity (Palacio, etal, 2014).One of mangroves found in Surabaya East Coastal(Pamurbaya), East Java, Indonesia is the mangroveRhizophora mucronata. This mangrove species isindigenous mangroves that ethno-botanicallypopular used as a pain reliever and dyes naturalwood. Secondary metabolites contained in theleaves, bark, stems, roots, and fruit are different inquantity. The content of secondary metabolites inplant commonly used as a medicine is from generalpart of the bark. Therefore, on the basis ofchemotaxonomic and ethno-botany of mangroves R.mucronata, this study aims to explore the bioactivityof antioxidant from the stem bark of R. mucronata.